Validation and public health modelling of risk prediction models for kidney cancer using the UK Biobank. (7th October 2021) - Harrison, Hannah; Pennells, Lisa; Wood, Angela; Rossi, Sabrina H.; Stewart, Grant D.; Griffin, Simon J.; Usher‐Smith, Juliet A.
Abstract : Objectives: To externally validate risk models for the detection of kidney cancer, as early detection of kidney cancer improves survival and stratifying the population using risk models could enable an individually tailored screening programme. Methods: We validated the performance of 30 existing phenotypic models predicting the risk of kidney cancer in the UK Biobank cohort ( n  = 450 687). We compared the discrimination and calibration of models for men, women, and a mixed‐sex cohort. Population level data were used to estimate model performance in a screening scenario for a range of risk thresholds (6‐year risk: 0.1–1.0%). Results: In all, 10 models had reasonable discrimination (area under the receiver‐operating characteristic curve >0.60), although some had poor calibration. Modelling demonstrated similar performance of the best models over a range of thresholds. The models showed an improvement in ability to identify cases compared to age‐ and sex‐based screening. All the models performed less well in women than men. Conclusions: The present study is the first comprehensive external validation of risk models for kidney cancer. The best‐performing models are better at identifying individuals at high risk of kidney cancer than age and sex alone; however, the benefits are relatively small. Feasibility studies are required to determine applicability to a screening programme.